Proceedings of the Highly Specialized Seminar on Symmetries in Nuclear Structure : (World Scientific, 2004)
The Highly Specialized Seminar on "Symmetries in Nuclear Structure", held in Erice, Italy, in March 2003, celebrated the career and the remarkable achievements of Francesco Iachello, on the occasion of his 60th birthday. Since the development of the interacting boson model in the early 1970s, the ideas of Iachello have provided a variety of frameworks for understanding collective behaviour in nuclear structure, founded on the concepts of dynamical symmetries and spectrum-generating algebras. The original ideas, which were developed for the description of atomic nuclei, have now been successfully extended to cover spectroscopic behaviour in other fields, such as molecular or hadronic spectra. More recently, the suggestion by Iachello of critical point symmetries to treat nuclei in shape/phase transitional regions has opened an exciting new front for both theoreticians and experimentalists.